Role of Hospital Management on Minimization Risks of Nosocomial Infections - Parsia, Yasaman; Puteri Fadzline, Muhamad Tamyez (IEOM Society International, 2018)
Despite the developments on human health and hospital management sciences, many health risks in hospitals should be well-thought-out; especially Nosocomial Infection (NI) (which is acquired by patients during hospitalization period). NIs add huge financial burden for patients, healthcare facilities, and society, raise patient mortality rates, prolong hospital stays, increase resistance to antimicrobials, and etc. It is studied and verified by previous researchers that a hospital management could play a noticeable role to control NI. However, the hospital management, hospital architecture, and ways of microbiological infection control are still demanding more studies and developments to be able to omit the NI risks. There is a need for more studies with the focus on minimizing NIs risks. This research has benefited from a qualitative research method, reviewing the existing literature, to list some of the critical factors in field of hospital management to prevent NI risks. Therefore, it is found that there are different criteria which need to be considered by hospitals and healthcare managers in cooperation by hospital architects. Some of the factors which the literature suggests are suitable equipment and their possible locations, light, air ventilation, functional distance between patients, ward types and designs. However, from the result of this study, the authors would like to highlight their finding on the importance of hospital architectural layout and their wards’ places or configuration of them to minimize NIs. To rephrase, architectural layout design of hospitals and their wards places or configuration of them could moderate the NIs rate, increase speed of patient recovery and financial profit etc. Therefore, the finding of this research, as a hypothesis, could be explored more by future studies.